Factors Affecting Retirement Preparedness Of Urban Young Adults In Malaysia The Mediating Role Of Temporal Construal Level. - Poh, Kee Cheng (2024)
There are numerous studies done on retirement preparedness and many have confirmed the benefits of being adequately prepared for the golden years, not just financially, but socially and psychologically as well. The bulk of these studies, however, have focused on the retiring population. Few studies, if at all, are done on youth on how they view retirement preparedness and how they are preparing for this inevitable event in their life. This study aims to identify and examine, in particular, the impact of the various communication factors on retirement preparedness [communication effectiveness, communication frequency, communication informativeness, communication persuasiveness, attitude, influence (family and peer)] as well as financial literacy and demographic factors – on urban young adults in Malaysia as well as how they are mediated by temporal construal level, a theory that espouses on people’s behavioural patterns based on the urgency of how they perceive a future event, like retirement as in the case of this study. For example, when people deliberate on the distant future (high construal level), they would construe positions and situations more abstractly as opposed to the near future (low construal level) where more concrete actions need to be taken. A total of 421 usable responses were collected and incorporated into the data analysis. The IBM SPSS for Windows Version 25.0 and Partial Least Squares-Structural Equation Modeling (PLS-SEM) were employed to check the nature of data, empirically test the research model, simultaneously analyse the relationships as well as answer the research questions advanced in this study.